Political and Religious Contributions in Economic Development - Lia Kian (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
The great conclusion of this paper is to prove the synergy between religion and politics in the economic development of a State. The more polarized the system of ethical-religious and political beliefs, the more help the economic development of a State. Based on the discourse on the religion and politics of the author in the direction of Beng-Lan Goh (2006), Wilson Erin K (2014), and Melleuish Gregory (2014) explaining the ideology of the state as an alternative logic forming religious symbolism from capitalist exploitation or commoditization, the best civilian politics in serving the people's welfare by rejecting the dichotomy of morality and interest systems, as well as religious and political understanding limits the capacity of religious clerics and actors in their significant influence on religious actions and rituals to the political sphere that greatly affects economic growth. The authors oppose the opinions of Bin Hassan (2007), San Juan (2011), Martinelli (2013) and Faux Jeff (2004) explaining that Effects of Islamic revival around the world in the competition of political power that directly and indirectly contribute to the development of Islam in politics, the United States and transnational geopolitical interests as a consequence of the contradiction between emerging and conservative nationalist impulses, the United States Congress that has successfully influenced key decisions on regulatory policy, has so far weakened existing systems and American economic politics flourish across borders, the same that happens in today's globalized economy. The data used in this paper comes from secondary data obtained from books, magazines, the Internet and other documentation relating to the study of the problems and this paper. This writing is descriptive qualitative with the approach of the research library.